ANALYSIS OF THE BODY COMPOSITION OF POLE DANCE WOMEN (Fiep Bulletin - online, 2017)
This study had as the mean goal analyzes and compare the real effects of a Pole Dance training in the bodycomposition of its performers, for six months they had two classes a week with one hour of training in each one, the evaluationwas established with pre- and post-test through anthropometry, circumferences, skinfold thickness and bone diameter, all theresearch was conducted in Studio “Art Fitness” and significant changes p?0,05 were found, there were the fractions ofcomponents, fat percentage, fat weight, the residual weight, bone weight and muscle weight, changes related to fat percentage,fat mass and muscle mass could be clearly seen. Explicit changes in averages, standard deviation and value of p = 0.05 for eachcollection used in the evaluation could be noted. Getting to the conclusion of the real health benefits that are possible by thetraining program of Pole Dance demonstrated through significant changes in body composition.